Double Adjacent Ventral Slots in Cervical Disc Extrusion with Epidural Haemorrhage in Four French Bulldogs - Olender, Magdalena; Couturier, Jérôme; Couturier, Laurent; Gatel, Laure; Brissot, Hervé (VCOT Open, 2022)
Four French bulldogs were presented with a history of cervical pain and/or signs of myelopathy and were diagnosed with an acute cervical intervertebral disc extrusion (IVDE), associated with epidural haemorrhage (EH). The lesion was classified as IVDE with EH by a board-certified radiologist based on contrast-enhanced computed tomography images. All dogs were treated with two adjacent ventral slots that confirmed diagnosis. The decompression was assessed by measurement of the amount of residual material on computed tomography studies, and the outcome was evaluated by clinical recheck. All dogs recovered uneventfully after the surgery. This case series describes the first detailed report of extensive cervical IVDE with EH where double adjacent ventral slots was used in a treatment of such lesion.
Keywords: neurosurgery; canine; ventral slot; epidural haemorrhage; disc extrusion